Kami memimpin, menjangkau bintang, meraih mercu ([Minden], Pulau Pinang Penerbit Universiti Sains Malaysia, 2008)
Aim and objective of developing university program and educational revolution at Universiti Sains Malaysia; speeches.
Includes bibliographical references.